Neurological Involvements in COVID-19: A hospital-based study - Montazerlotfelahi, Hadi; Norouzi, Mahsa; Askarimoghaddam, Forough; Hashemnejad, Mohammad Amin; Bastan Sarabi, Niusha; Qorbani, Mostafa; Dehghani, Mahdieh; Ashrafi, Mahmoudreza; Mostafavi, Keihan; Haj Mohamad Ebrahim Ketabforoush, Arsh; Nikkhah, Ali (Iranian Journal of Child Neurology, 2023)
Objectives The SARS-CoV-2 pandemic is the most challenging crisis in the contemporary world. Besides severe pulmonary involvement, the disease also has several extrapulmonary manifestations, and new signs and symptoms are associated with it every dayThe present study aimed to inquire about the frequency of neurological manifestations and risk factors of COVID-19. Materials & Methods This retrospective, descriptive study included patients with neurological involvement admitted to the Alborz University of Medical Sciences academic hospitals from March 2020 to July 2020 with confirmed COVID-19 infection. The data included in the analysis were the patient’s demographic information, underlying diseases, neurological manifestations, and laboratory findings. Results The study included ninety-five patients with a mean age of fiftynine. Neurological symptoms and signs were observed in 91.6% and 10.5% of the patients, respectively. The most frequently associated neurological symptoms of COVID-19 were fatigue (49.5%), headache (47.4%), and dizziness (45.3%). Furthermore, the most common neurological involvements included gait disorders (6.3%), cerebellar dysfunction (4.2%), and cerebrovascular accidents (3.15%). Positive troponin was shown to be the strongest predictor of neurological signs (OR=21, P=0.017), followed by WBC≥15,000 (OR = 20.75, P=0.018) and a history of respiratory disease (OR=7.42, P=0.007).